Embryonic cardiomyocytes beat best on a matrix with heart-like elasticity: scar-like rigidity inhibits beating - Engler, Adam J. (2008)
Fibrotic rigidification following a myocardial infarct is known to impair cardiac output, and it is also known that cardiomyocytes on rigid culture substrates show a progressive loss of rhythmic beating. Here, isolated embryonic cardiomyocytes cultured on a series of flexible substrates show that matrices that mimic the elasticity of the developing myocardial microenvironment are optimal for transmitting contractile work to the matrix and for promoting actomyosin striation and 1-Hz beating. On hard matrices that mechanically mimic a post-infarct fibrotic scar, cells overstrain themselves, lack striated myofibrils and stop beating; on very soft matrices, cells preserve contractile beating for days in culture but do very little work. Optimal matrix leads to a strain match between cell and matrix, and suggests dynamic differences in intracellular protein structures. A ‘cysteine shotgun’ method of labeling the in situ proteome reveals differences in assembly or conformation of several abundant cytoskeletal proteins, including vimentin, filamin and myosin. Combined with recent results, which show that stem cell differentiation is also highly sensitive to matrix elasticity, the methods and analyses might be useful in the culture and assessment of cardiogenesis of both embryonic stem cells and induced pluripotent stem cells. The results described here also highlight the need for greater attention to fibrosis and mechanical microenvironments in cell therapy and development.